2019
DOI: 10.1371/journal.pone.0223794
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of Escherichia coli detergent-resistant membranes (DRM)

Abstract: Membrane microdomains or lipid rafts compartmentalize cellular processes by laterally organizing membrane components. Such sub-membrane structures were mainly described in eukaryotic cells, but, recently, also in bacteria. Here, the protein content of lipid rafts in Escherichia coli was explored by mass spectrometry analyses of Detergent Resistant Membranes (DRM). We report that at least three of the four E. coli flotillin homologous proteins were found to reside in DRM, along with 77 more proteins. Moreover, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 51 publications
(77 reference statements)
5
19
0
Order By: Relevance
“…It is conceivable that under stress conditions, for example the exposure to high temperature when the lapC mRNA is made more, the LapB/FtsH activity is repressed when LapC is more. Supporting our results of increased accumulation of LapC at high temperature are independent proteomic analysis data of total E. coli proteome from high temperature or other stress conditions [63,64]. In line with such arguments are findings that LpxC is more rapidly degraded at lower temperatures than at higher temperatures correlating it with doubling time of E. coli [56].…”
Section: Discussionsupporting
confidence: 86%
“…It is conceivable that under stress conditions, for example the exposure to high temperature when the lapC mRNA is made more, the LapB/FtsH activity is repressed when LapC is more. Supporting our results of increased accumulation of LapC at high temperature are independent proteomic analysis data of total E. coli proteome from high temperature or other stress conditions [63,64]. In line with such arguments are findings that LpxC is more rapidly degraded at lower temperatures than at higher temperatures correlating it with doubling time of E. coli [56].…”
Section: Discussionsupporting
confidence: 86%
“…We first tested AcrA, the efflux pump involved in the transport of a wide range of substrates including aminoglycosides (45) and YidC, an essential inner membrane protein required for proper insertion of integral inner membrane proteins (46). Both proteins were indeed previously identified in E. coli inner-membrane DRM fractions often biochemically associated with FMM and shown to display HflC-type pattern of polar localization when fused to fluorescent proteins and expressed from plasmids (35,47). However, when expressed from their native chromosomal context, we could not detect any distinct AcrA-GFP nor YidC-GFP localization nor any significant co-localisation with HflC in exponential or stationary phase conditions (Sup.…”
Section: Yajc Interacts and Colocalizes With Hflc And Contributes To ...mentioning
confidence: 99%
“…HflC and QmcA are detected in E. coli membrane fractions resistant to solubilization by non-ionic detergents (detergent-resistant membranes or DRM) that are often used as - debatable - proxies for FMMs (3134). Moreover, fluorescent microscopy showed that E. coli SPFH proteins HflC and QmcA are localized in discrete polar or lateral membrane foci (35). This raised the possibility that E. coli SPFH proteins could localize in inner-membrane FMMs and regulate important cellular processes (36).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2b, Table S2). Apart from phage-related genes, those in the chromosome were involved in metabolism (acetolactate synthase, ABC transporter substrate-binding protein), DNA replication (DNA primase and ATP-dependent helicase), signalling (hybrid sensor histidine kinase (rpfC), two-component system response regulator (rpfG) [58] and SPFH/Band 7/PHB domain protein [59,60]), gene expression (helix-turn-helix domain containing protein, transcriptional regulator Crp), cell wall growth/lysis [61] (lysozyme and UDP-N-acetylmuramoyl-l-alanyl-d-glutamate-−2, 6-diaminopimelate ligase), peptidase, ATP synthase and pathogenesis (zonula occludens toxin, Fig. 2c, Table S2).…”
Section: Whole Genome Comparison Between Costa Rican and Apulian Isolatesmentioning
confidence: 99%